Europe at the Polls
XVIII, 318 p.
Keywords: In election after election for the European parliament there has been a growing ability for voters to deal with Europe, by-passing categories that are still used to think about essentials political issues within individual countries. Europe at the Polls highlights this liberation of the 'European Question' from the old left-right conflicts that have marked political life within the 15 members of the European Union. Across national borders, this study of those elections shows that diverse trends are taking root in homes, towns, and in the workplace, and are reflected in the electoral geography at the level of the European Union. The increasing strength of Green parties, the continued decline of European Communism, and ethno-regionalism are just some of the issues that this book explores with the hope that Europe can begin constructing a real European public space within which a strong link to citizens can be woven.